Narrative Literature Review: Policy Implementation in Reducing Maternal Mortality Rate - Asri Nur Aina (Universitas Negeri Makassar, 2024)
Maternal mortality during pregnancy, childbirth, and postpartum is a critical indicator of healthcare quality in a country. Despite various efforts by the Indonesian government, the maternal mortality rate (MMR) remains alarmingly high, as evidenced by data from the Maternal Perinatal Death Notification (MPDN) showing an increase from 4,005 deaths in 2022 to 4,129 deaths in 2023. This narrative literature review aims to analyze the implementation of policies to reduce maternal mortality in Indonesia, identify challenges, and provide recommendations for improving policy effectiveness. The study reviewed 15 previous research articles, selected using the Publish or Perish application with a focus on publications from 2020 to 2024. Key findings indicate that Community Health Centers (Puskesmas) play a pivotal role in providing comprehensive antenatal care (ANC) and implementing special programs like Childbirth Planning and Prevention of Complications (P4K) and Maternity Insurance (Jampersal). Effective stakeholder coordination, community empowerment, and continuous evaluation and adjustment of health programs were identified as critical factors in successful policy implementation. The research concludes that a comprehensive and sustainable approach, involving enhanced coordination among stakeholders, participatory community programs, equitable healthcare services, and regular program evaluations, is essential to significantly reduce maternal mortality and improve maternal and child health in Indonesia. The findings underscore the need for ongoing efforts to address the persistent challenges and ensure the effective implementation of maternal health policies.